Group Therapy, Spiritual Issues, and Vietnam Veterans - Lapierre, Lawrence L. (Journal of religion and health, 1997)
This article describes a form of therapy that focuses on the spiritual dimension of the experience of American military veterans. Since definitions of spirituality abound, it is important that therapists be able to work with multiple understandings of spirituality simultaneously. Such veterans often resist facing, much less integrating, the spiritual dimension of their experience in therapy. A process is described that uses a VA Chaplain as a co-therapist on a monthly basis in an ongoing group. Telling Biblical stories and parables, in the context of therapy, is reported as a valuable means to enable clients to deal with their spiritual issues.